Erbium-Doped Fiber Amplification Assisted Multi-Wavelength Brillouin-Raman Fiber Laser - Ismail, Aiman; Mohammad Helmi, Hazwani; Zaini Jamaludin, Md; Abdullah, Fairuz; Hadi Sulaiman, Abdul; Pin Jern, Ker (International Journal of Engineering and Technology, 2018)
Multi-wavelength fiber laser based on Brillouin scattering in optical fiber has the potential of application in dense wavelength division multiplexing (DWDM) system. To enhance the performance of the fiber lasers, researchers proposed usages of erbium, or Raman amplification techniques. In an earlier work, it was reported that extracting residual Raman pump out of the laser cavity improves the performance of a multi-wavelength Raman fiber laser. In this paper, we proposed a setup utilizing the residual Raman pump to pump an erbium-doped fiber in multi-wavelength Brillouin-Raman fiber laser. Results show that the additional erbium-doped fiber is capable of amplifying the propagating Brillouin Stokes by more than 15-dB. This in turn helps in achieving lower stimulated Brillouin threshold and subsequently allow for higher number of Brillouin Stokes lines to be generated.Â Â Â